Knowledge, attitude and practice towards evidence based practice among clinical physical therapists of Khyber Pakhtunkhwa - Qarib Ullah; Jahangir Khan; Mansoor Ahmad; Sana Ullah; Husan Hayat; Huma Balqias; Madiha Anees (Rehman Journal of Health Sciences, 2019)
Introduction: Evidence Based Practice (EBP) constitutes of clinical skills, patients values and high-quality clinical research for decision-making in-patient care. EBP provide better use of resources for improving the emerging questions in clinical setup hence improving the effectiveness of the treatment. The physical therapists and physical therapist assistants shall provide services which increase patients care and hence improve quality of life.